2021
DOI: 10.1111/joss.12720
|View full text |Cite
|
Sign up to set email alerts
|

Using check‐all‐that‐apply to evaluate wine and food pairings: An investigation with white wines

Abstract: Growing consumer interest in food and wine pairing leads to a need for more studies to be conducted evaluating consumers' perception of food pairings. Many studies have used trained panelists to evaluate food and wine pairings; however, this study sought to determine how consumers evaluate food and wine pairings using the check‐all‐that‐apply (CATA) method. The participants (n = 112) were asked to evaluate five white wines for their liking of the wine, their sensory perception of the wines and identify which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…We controlled for several alternative drivers of participants' reactions to the stimuli. We collected behavioral data of the participants, including their drinking capacity and drinking frequency, as these are often used as control variables in sensory studies related to alcoholic beverage consumption (Jantzi, Hayward, Barton, Richardson, & McSweeney, 2020; Moss, Barker, & McSweeney, 2021; Ribeiro et al, 2021). Participants' sociodemographic characteristics, including age and gender, were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…We controlled for several alternative drivers of participants' reactions to the stimuli. We collected behavioral data of the participants, including their drinking capacity and drinking frequency, as these are often used as control variables in sensory studies related to alcoholic beverage consumption (Jantzi, Hayward, Barton, Richardson, & McSweeney, 2020; Moss, Barker, & McSweeney, 2021; Ribeiro et al, 2021). Participants' sociodemographic characteristics, including age and gender, were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…Also, hydration status has been found to aid wound healing. As such the researchers' past studies have investigated the sensory properties of protein‐enhanced thickened ice cream (McDowell et al, 2022; Moss et al, 2023). These studies identified that thickened ice cream could be enhanced with whey protein up to 10% by volume before the sensory properties are negatively impacted and the products were still acceptable for those living with dysphagia based on IDDSI spoon tilt test.…”
Section: Introductionmentioning
confidence: 99%
“…Both projective mapping and CATA have been used to study a myriad of different products, see the references in the book by Varela and Ares (2014), or (Beekman & Seo, 2022; Lin et al, 2022; Melendrez‐Ruiz et al, 2022; Moss et al, 2022a; O'Brien et al, 2022; Selani et al, 2022; Varela et al, 2022) for just a few very recent references studying some local and particular products. It is remarkable that out of the 195 works using projective mapping that were included in the recent review by Moss and McSweeney (2022), only 11% used both projective mapping and CATA.…”
Section: Introductionmentioning
confidence: 99%